2008
DOI: 10.1038/nature07054
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae ATM orthologue suppresses break-induced chromosome translocations

Abstract: Chromosome translocations are frequently associated with many types of blood-related cancers and childhood sarcomas. Detection of chromosome translocations assists in diagnosis, treatment and prognosis of these diseases; however, despite their importance to such diseases, the molecular mechanisms leading to chromosome translocations are not well understood. The available evidence indicates a role for non-homologous end joining (NHEJ) of DNA double-strand breaks (DSBs) in their origin. Here we develop a yeast-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
85
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 30 publications
12
85
3
Order By: Relevance
“…Rad53 and Dun1 may phosphorylate proteins at the sites of DNA damage in a Sae2-dependent manner. For example, Dun1 was implicated in suppressing DSB-induced chromosomal translocations in the same study that demonstrated a role for Sae2 and its DNA damage-induced phosphorylation (14). Clearly, identification of the relevant substrates of Rad53 and Dun1 that are specifically mediated by Sae2 would be essential to understand the function of the interactions reported here.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Rad53 and Dun1 may phosphorylate proteins at the sites of DNA damage in a Sae2-dependent manner. For example, Dun1 was implicated in suppressing DSB-induced chromosomal translocations in the same study that demonstrated a role for Sae2 and its DNA damage-induced phosphorylation (14). Clearly, identification of the relevant substrates of Rad53 and Dun1 that are specifically mediated by Sae2 would be essential to understand the function of the interactions reported here.…”
Section: Discussionmentioning
confidence: 66%
“…Mutation of five SQ/TQ sites of Sae2, sae2 2,5,6,8,9 , which conform to the consensus phosphorylation motif of Mec1 and Tel1, eliminated the bulk of its DNA damage-induced phosphorylation and caused persistent Rad53 activation in response to transient DNA damage treatment similar to the deletion of SAE2 (9,13). Furthermore, these sae2 mutations caused a defect in suppression of chromosomal translocation mediated by nonhomologous end joining (14). Interestingly, mammalian CtIP, ortholog of Sae2, is phosphorylated by ATR and ATM (15)(16)(17), which are orthologs of Mec1 and Tel1, respectively.…”
mentioning
confidence: 99%
“…Consistent with a role in limiting DSB persistence, genetic deficiencies in the MRE11-RAD50-NBS1 complex have been shown to cause persistent coding DSB ends during repair of inverted V(D)J recombination substrates (6). Regarding end tethering, the MRE11-RAD50-NBS1 complex promotes in vitro DNA tethering and EJ via DNA ligase III (15, 18 -20), and the MRE11-RAD50-XRS2 complex is important in Saccharomyces cerevisiae for maintaining spatial continuity of a broken chromosome and for suppressing chromosomal translocations (63,64). In summary, we suggest that the functions of DNAPKcs kinase activity and RAD50 in limiting the persistence of DSBs and/or promoting correct end tethering could contribute to their roles in limiting incorrect end use during EJ of multiple DSBs.…”
Section: Discussionmentioning
confidence: 99%
“…The HO-inducible translocation assay was performed according to Lee et al (2008). Briefly, log-phase cells were sonicated, cell number was determined using a Coulter counter (Beckman Dickinson), and serial dilutions were plated on C-Ura dropout plates containing galactose to induce HO expression.…”
Section: Gross Chromosomal Rearrangement and Translocation Assaysmentioning
confidence: 99%
“…For Tel1p's role in both the DDR and telomere metabolism, significant questions remain. While the kinase was once thought to be functionally redundant with Mec1p in the DDR, recent studies have identified distinct Mec1-independent roles for Tel1p in checkpoint signaling (Mantiero et al 2007), replication fork stability (Doksani et al 2009), and the suppression of genome rearrangements (Lee et al 2008). None of the mechanisms underlying these roles are well understood.…”
mentioning
confidence: 99%